Perabaikan Tegangan Jatuh Instalasi Listrik Satu Fasa Di Area Persawahan Dengan Beban Pompa Air - Nugraha, Danang Riyadi, Hasyim Asy'ari, ST.MT (2016)
The electrical installation is a network equipment that generate, use, modify, organize, assign, collect or distribute electricity. Installation of electrical lighting and power in residences, installations in industry, certain household, marine vessels, even the installation of electricity in the area of rice fields. Some real cases encountered in the field on a voltage drop (voltage drop) on the installation of electricity in the area of rice fields, resulting in electrical machinery equipment performance in the area of rice fields are not running optimally and can damage electrical equipment users, in this case the water pump. The length of the pull and great conductors used to be very influential in the installation. To resolve the problem in this case study needs analysis related to the type of conductor, conductor diameter and the addition milai tool that minimizes voltage drop which is still within the tolerance of PLN (10%). The method used is to configure the load and cross-sectional area by using software electrical voltage drop calculations to simulate real network of pumps in the area of rice fields and through the selection of a budget plan is needed. The results showed with the reconfiguration of the load current on one phase of 13.6A and use LVTC aluminum cables with cross-sectional area of 16 mm and the percentage of voltage drop of 3.89% or 204.72 volt low voltage, the cost cable replacement 210m Rp. 1,890,000. To save the budget can also use stavolt servo 5 KVA capacity to stabilize the voltage to 220 volts, with a budget of Rp. 1,750,000.